STRATEGI PENINGKATAN PRODUKSI TOMAT DI KECAMATAN SEMENDE DARAT LAUT KABUPATEN MUARA ENIM - Oktarina, Yetty; Mustagfiri, Mustagfiri; Munajat, Munajat (AGROTEKSOS; Vol 35 No 3 (2025): Jurnal Agroteksos Desember 2025, 2025)
Tomatoes are horticultural vegetables and one of the seasonal crops with a short harvest period. However, tomato production yields can be improved with adequate water channels and sunlight. Tomato cultivation by farmers has promising production results, especially in terms of income generated from tomato cultivation. The purpose of this study is to analyze strategies for increasing tomato production in Semende Darat Laut District, Muara Enim Regency. The results of the study show that IFAS and EFAS place the strategy for increasing tomato production in Quadrant I (SO) in the SWOT diagram with coordinate values (2.046; 1.964). This position indicates very favorable conditions, so the most appropriate strategy to apply is an aggressive strategy (SO), which is to utilize all internal strengths to capture and maximize external opportunities. This strategy is aimed at optimizing land use, increasing productivity through the application of technology, strengthening farmer institutions, and utilizing government support and market opportunities to increase production, competitiveness, and sustainability of tomato farming in Semende Darat Laut Subdistrict, Muara Enim Regency.